Orientation, Supervision and University Student-teacher Performance in Oyo State, Nigeria - Oredein, Afolakemi Olasumbo; Oyetade, Monilola Dasola (Advances in Social Sciences Research Journal, 2018)
This study examined the influence of teaching practice orientation and supervision on university student-teachers’ performance in selected public secondary schools in Ibadan. The population consisted of all the penultimate and final year of the Faculty of Education students in the sampled instituitons. The sample was made of two hundred (200) student-teachers from 300 and 400 levels respectively and twenty cooperating teachers making two hundred and ten (210). Multistage and simple random sampling techniques were used to select the sample. For data collection, developed structured questionnaire was adopted and three research questions and two research hypotheses were formulated and tested at 5% level of significance. The instrument was given face validity and the reliability Cronbach Alpha was 0.86. Descriptive research design was used and the data collected was analyzed using descriptive and inferential statistics such as ANOVA and t-distribution test was used to analyze the gender difference. Among others, the result revealed a combined influence of teaching practice orientation and supervision (F=10.87, P<0.05) on the university possessive-teacher performance during the teaching practice exercise. It was recommended that teaching practice committee of each university should make sure that possessive-teachers are posted to the practicing schools where they are needed.